Characteristics and predictors of breast milk iodine in exclusively breastfed infants: Results from a repeated-measures study of iodine metabolism - Guo, Wenxing; Wu, Wen; Gao, Min; Yang, Ying; Pearce, Elizabeth N.; Li, Shaohan; Ren, Zhiyuan; Zhang, Naifan; Zhang, Kexin; Pan, Ziyun; Zhang, Wanqi (Frontiers in Nutrition, 2022)
Background The iodine supply of exclusively breastfed infants entirely depends upon breast milk. Changes in breast milk iodine affect infants’ iodine nutritional status. This study aimed to comprehensively assess the characteristics and predictors of breast milk iodine concentration (BMIC). Materials and methods This 7-day iodine metabolism experiment was conducted in 25 exclusively breastfed mother-infant pairs. The duplicate portion method was used to measure the mother’s daily iodine intake from foods and water, and maternal 24-h urine excretion was assessed. We recorded the number of breastfeeds per mother per day and collected breast milk samples before and after each feeding. Results The median [quartile (Q)1–Q3 range] of BMIC was 115 (86.7, 172) μg/L. The BMIC before breastfeeding was generally higher than that after breastfeeding. Time-sequential analysis found that morning BMIC was most highly correlated with the prior day’s iodine intake. Breast milk samples taken in the afternoon or after midnight are closer to the median level of BMIC throughout the day. The number of breast milk samples needed to estimate the iodine level with 95% CI within precision ranges of ± 20% was 83 for a population, 9 for an individual, and 2 for an individual’s single day. Maternal total iodine intake (TII) and urine iodine were significantly associated with BMIC. 24-h urinary iodine excretion (24-h UIE) was found to be the best predictive indicator for the BMIC (β = 0.71, 95% CI: 0.64, 0.79). Conclusion BMIC is a constantly changing indicator and trended downward during each breastfeeding. Breast milk samples taken in the afternoon or after midnight are most representative. BMIC was significantly associated with recent iodine intake. Maternal 24-h UIE was the best predictor of BMIC.